Entrepreneurial and small business stressors, experienced stress, and well being - Perrewé, Pamela L.; Harms, Peter D.; Chang, Chu-Hsiang (Daisy) (Research in occupational stress and well being, 2020)
Volume 18 of Research in Occupational Stress and Well-Beingis focused on the stress and well-being related to Entrepreneurship and Small Businesses. This volume focuses on entrepreneurial and small business owners' stress, health, and well-being as it relates to personal, work, and success outcomes.